Modern methods of prevention and treatment of intrauterine adhesions (literature review) - P M Khirieva; L V Adamyan; S A Martynov (Гинекология, 2016)
Intrauterine adhesions (IUA) or Asherman's syndrome - multifaceted condition, which is being diagnosed with increasing frequency in recent years and a major cause of secondary infertility. Despite the widespread adoption of hysteroscopic adhesiolysis, the management of IUAs still presents a big challenge: the recurrence rate could be up to 62.5% in severe IUAs. The literature review highlights the current capabilities of surgical treatment, methods and means of prevention of recurrence, as well as the most promising research into the pathogenesis and treatment of Asherman's syndrome.